2023
DOI: 10.1038/s41380-023-02213-w
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular free water elevations are associated with brain volume and maternal cytokine response in a longitudinal nonhuman primate maternal immune activation model

Abstract: Maternal infection has emerged as an important environmental risk factor for neurodevelopmental disorders, including schizophrenia and autism spectrum disorders. Animal model systems of maternal immune activation (MIA) suggest that the maternal immune response plays a signi cant role in the neurodevelopment and behavioral outcomes of offspring. Extracellular free water is a measure of freely diffusing water in the brain that may be associated with neuroin ammation and impacted by MIA. The present study evaluat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 91 publications
1
3
0
Order By: Relevance
“…1b-e) 51 . Notably, this range aligns with the lower spectrum of brain tissue stiffness, which typically spans from 0.1 to 2 kilopascals 52 . With time, the CorticOs stiffen, likely due to continuous ECM deposition and/or fibrillation.…”
Section: Resultssupporting
confidence: 58%
See 2 more Smart Citations
“…1b-e) 51 . Notably, this range aligns with the lower spectrum of brain tissue stiffness, which typically spans from 0.1 to 2 kilopascals 52 . With time, the CorticOs stiffen, likely due to continuous ECM deposition and/or fibrillation.…”
Section: Resultssupporting
confidence: 58%
“…To test this directly, we employed Diffusion-Weighted Magnetic Resonance Imaging (DW-MRI) to compare differences in the structural organization of day18 control, LIS1 +/− , and MMP-treated LIS1 +/− CorticOs. Notably, DW-MRI was previously shown to provide noninvasive means for identifying changes in ECM organization 51 , extracellular free water component 52 , stiffness, and other structural parameters 53 . To examine the sensitivity of DW-MRI, groups of control, LIS1 +/− , and MMP-treated LIS1 +/− containing multiple CorticOs were placed in separate wells and scanned (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Large epidemiologic studies have shown that maternal immune activation (MIA) caused by prenatal exposure to bacterial or viral infections increases the risk of ASD (Careaga et al 2017 ; Lombardo et al 2018 ). Animal researches have revealed that MIA exacerbates ASD-like behavioral abnormalities by causing brain inflammation in offspring (Cieślik et al 2023 ), and they have also identified some potential mechanisms, such as the inflammatory injury of cytokines like interleukin (IL)-6 (Brown et al 2014 ; Lesh et al 2023 ) and IL-17 (Bagcioglu et al 2023 ; Sarieva et al 2023 ) in the brain. It is important to note that blocking IL-6 (Smith et al 2007 ) or IL-17 A (Reed et al 2020 ) signaling effectively alleviated behavioral abnormalities in ASD mice, although the specific neural mechanisms are still unclear.…”
Section: Introductionmentioning
confidence: 99%